Ім'я "ΤΑỦΤὉΝ" у теологічній ономасіології Діонісія Ареопагіта - Попов, В. (Схід, 2012)
У статті розглядається проблема тлумачення змісту поняття "тотожність (ταủτоν)" у "Corpus Areopagiticum", яке представлено в ньому як одне з Божественних імен. Проведено історико-філософський аналіз уривку з твору "Про Божественні імена" з наведенням першоджерела та існуючих перекладів. На цій підставі здійснено перший переклад цього уривку українською мовою. Автором зроблено висновок про апофатичний характер діонісієвої ономасіології, що стала однією із засад візантійської філософії. In the article the problem ofinterpretati on of the notionof "identity (ταủτоν )" is examined in the "Corpus Areopagiticum", which is presented in it as one of the Divine names. The historical and philosophical analysis of complex of teologo-philosophical the passage from the works of "The Divine names" is conducted by research of both original sources and the existing translations. On th is basis, made the first translati on of the text in the Ukraine language. The author concludes apophatic character Dionysius'еs onomatology that has become one of the foundations of a byzantine philosophy.